Reporting of outcomes in randomized controlled trials on nail psoriasis: a systematic review. (1st March 2018) - Busard, C.I.; Nolte, J.Y.C.; Pasch, M.C.; Spuls, P.I.
Summary: Background: Harmonization of outcome measures is needed to increase the value of clinical trials on nail psoriasis. Objectives: To provide the first step in core outcome set (COS) development for nail psoriasis. Methods: A systematic review was performed to identify outcome instruments and corresponding outcome domains used in (ongoing) randomized controlled trials. Results: Identified outcome domains included clinical signs, quality of life, symptoms and delivery of care. The Nail Psoriasis Severity Index (NAPSI) was the most commonly used measure to assess clinical signs (74% of studies). Other outcome instruments used included the Nail Area Severity score, composite fingernail score, a Physician's Global Assessment, individual nail features or a combination of these. Heterogeneity in type and reporting (e.g. NAPSI 50, NAPSI 75) of outcome instruments was high and characteristics were often insufficiently reported. In total 43% of studies assessed quality of life, with 3% of studies using a nail psoriasis‐specific tool. Assessment of symptoms and delivery of care was limited. Conclusions: Heterogeneity in the type and reporting of nail psoriasis outcome instruments needs to be addressed in the process towards COS development. Sufficient reporting of instrument characteristics should be encouraged. As nail psoriasis is generally assessed secondarily to psoriasis of the skin or joints, collaboration between different research groups in COS development is needed.